Relationship Between Emotional Intelligence and Psychological Distress Among Nursing Students in College of Nursing Gombe State, Nigeria - Musa, Abubakar; Dauda, M. Kala; Saba, Y. Aisha (Kashere Journal of Education, 2022)
The relationship between Emotional Intelligence and psychological distress among students in College of Nursing, Gombe state. The research design for the study was Correlation design. A Null hypothesis was formulated to guide the study. The population was all the students of the College of Nursing Gombe. ‘Schutte Self-Report Emotional Intelligence Test’ (SSEIMT) ‘Scale and ‘Kessler Psychological Distress Scale’ were adapted and used as Instruments for data collection. Two experts from the department of Educational Foundation Abubakar Tafawa Balewa University, Bauchi validated the two instruments. The internal consistency of the instruments showed Cronbach’s, for emotional intelligence scale is 0.86 and 0.64 for Psychological Distress scale respectively. Two hundred and twenty-five (225) Nursing students participated in the study. Ethical approval was obtained from the College Management. Pearson Product Moment Correlation (PPMC) was used to analyze the Null hypothesis. The findings of the study revealed that, most of the participants had high level of emotional intelligence and were experiencing low degree of psychological distress; it was concluded that the higher the level of emotional intelligence the lower experiencing of psychological distress by the Nursing students. Therefore, it is recommended that further exploration to better understanding of emotional intelligence and Psychological distress. Moreover, there is need to include coping strategies in the Nursing curriculum to enhance managing the emotional intelligence.